A new species of the genus Acinopus Dejean, 1821 from west of Iran (Coleoptera; Carabidae; Harpalini) with a key to species of Iran - Azadbakhsh, Saeed; Wrase, David W. (Zootaxa, 2016)
A new species of the genus Acinopus Dejean, 1821, namely Acinopus (Acinopus) zagrosensis sp. n., is described on the basis of specimens collected from west Iran (type locality: Iran, Fars province, Zagros Mts., Sepidan env., 2060 m). The new species is compared with closely related species. A key for the identification of species of genus Acinopus in Iran is provided.